2018
DOI: 10.1055/a-0600-2979
|View full text |Cite
|
Sign up to set email alerts
|

Die Bedeutung des MRT nach geschlossener Reposition der traumatischen Hüftgelenkluxation im Kindes- und Jugendalter

Abstract: MRI is gaining increasing importance following traumatic hip dislocation in children and adolescents. A missing chondral or osteochondral fragment in the CT scan does not exclude a labral lesion or interposition. Therefore, MRI following closed reduction is mandatory in any case.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…This imaging modality was able to identify all intraoperatively confirmed lesions preoperatively, while CT imaging underestimated posterior wall injuries given the later ossification of this structure during normal development. 16 , 17 In 2018, Strüwind et al 14 demonstrated the utility of MRI in identifying labral interposition following closed reduction of these dislocations, especially given that two of their patients who had a free body identified on CT had missed labral interpositions when subsequently managed operatively. Similar findings were reported by Thanacharoenpanich et al 28 in 2020, who found that not only did MRI capture all bony injuries also identified by CT, but MRI also identified one posterior acetabular injury and three labral entrapments that CT could not.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This imaging modality was able to identify all intraoperatively confirmed lesions preoperatively, while CT imaging underestimated posterior wall injuries given the later ossification of this structure during normal development. 16 , 17 In 2018, Strüwind et al 14 demonstrated the utility of MRI in identifying labral interposition following closed reduction of these dislocations, especially given that two of their patients who had a free body identified on CT had missed labral interpositions when subsequently managed operatively. Similar findings were reported by Thanacharoenpanich et al 28 in 2020, who found that not only did MRI capture all bony injuries also identified by CT, but MRI also identified one posterior acetabular injury and three labral entrapments that CT could not.…”
Section: Discussionmentioning
confidence: 99%
“…1,3,6,8,[10][11][12] While radiographs both pre and postreduction are established as standard of care in the management of this sort of injury, the role of computed tomography (CT) and especially magnetic resonance imaging (MRI) in the acute phase of managing traumatic hip dislocations in the pediatric population remains more heterogeneous. 6,[13][14][15] As a function of the developing skeleton's pattern of ossification, injuries in the skeletally immature may not be readily apparent on plain radiographs or even CT. Fabricant et al 16 demonstrated that posterior acetabular wall ossifi cation typically occurs around 12-13 years of age, just prior to the closure of the triradiate cartilage. Therefore, accurate imaging is critical to fully understand these inju ries, especially given that the majority are managed through closed reduction, in which direct visualization of intraarticular structures is impossible.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traumatic hip dislocations are exceedingly rare in childhood and adolescence (Macnicol, 2000;Mehlman et al, 2000;Kutty et al, 2001;Ayadi et al, 2008;Brandão et al, 2010;Bressan et al, 2014;Strüwind et al, 2018).…”
mentioning
confidence: 99%
“…Currently, conventional X-rays are established as the standard both before and after reduction. However, computed tomography (CT) and particularly magnetic resonance imaging (MRI) are attributed with a heterogeneous signi cance in the acute phase of traumatic hip dislocation (Vialle et al, 2005;Blanchard et al, 2016;Strüwind et al, 2018). Fabricant et al demonstrate that ossi cation of the posterior acetabular wall usually occurs between twelve and thirteen years of age (Fabricant et al, 2013), and that conventional X-rays and CT scans may not effectively depict the non-ossi ed, developing, cartilaginous portions of the immature acetabulum (Yang et al, 2023).…”
mentioning
confidence: 99%